the comparative analysis of indicators of quality of life and eyesight capacity among the patients after different types of eye mechanical injury - S. A. Kochergin; N. D. Sergeeva (Oftalʹmologiâ)
Purpose: the comparative evaluation of indicators of quality of life and eyesight capacity among groups of patients with different types of eye mechanical trauma for studying of the possibility of the authentic qualitative and quantitative analysis.Methods: 120 patients (101 men and 19 women) with a mechanical injury of an eye are included in research. the mean age was 42.3±17.4 years, from 18 to 74 years. Patients are divided according to the type of trauma: with a contusion — 67 patients (group A), with penetrating wounds — 53 patients (group B).Results: the study shows the expediency of early (at the stage of hospitalization) determination by the patient his own condition, in order to trace dynamics in indicators of quality of life, timely reacting to them, making changes in treatment tactics in the post- traumatic period.Conclusion: Profound attention from experts for definition of strategy of recovering is demanded by a pain syndrome and a psy- chological stress of patients. the individual approach provides competent application of questionnaires, as tools of the assessment of quality of life.